Geophysical Well Logs Applied to Geothermal Resource Evaluation Application des diagraphies à l'évaluation des ressources géothermiques - Fertl W. H. (Oil & Gas Science and Technology, 2006)
Well logging in the petroleum industry has been developed over five decades into a mature industry, whereas geothermal well logging is a relatively new enterprise. Fundamental differences also occur in the geologic environments and key objectives of both logging applications. Geothermal reservoirs are frequently in fractured igneous and metamorphic rocks, which contain hot water or stem at temperature exceeding 150°C. The discussion focuses on present day logging technology, geologic and reservoir engineering objectives, and qualitive and quantitative formation interpretation techniques for geothermal resource evaluation. Specific field case studies illustrate the interpretive state-of-the-art, including examples from the Geysers dry steam field in the Imperial Valley of California, hot water fields in California, Nevada, and Idaho, and the LASL Hot Dry Rock test project in the Valles Caldera of New Mexico. Les diagraphies dans les forages pétroliers ont atteint leur maturité, alors que le contrôle diagraphique des sondages géothermiques est une entreprise relativement nouvelle. Des différences fondamentales apparaissent aussi dans les environnements géologiques et dans les objectifs clés des deux types d'applications des diagraphies. Les réservoirs géothermiques se situent souvent dans les roches ignées ou métamorphiques fracturées qui contiennent de l'eau chaude ou de la vapeur à des températures dépassant 150 °C. L'exposé sera concentré sur les techniques actuelles d'enregistrements, les objectifs géologiques et liés à l'exploitation des réserves et sur les techniques qualitatives et quantitatives d'interprétation des formations pour l'évaluation des ressources géothermiques. Quelques cas particuliers illustrent l'état actuel des techniques d'interprétation avec des exemples pris dans le champ de vapeur sèche des geysers dans Imperial Valley de Californie, des champs d'eau chaude en Californie, Nevada et Idaho et le projet expérimental LASL Hot Dry Rock dans les Valles Caldera du Nouveau- Mexique.